2018
DOI: 10.1093/pm/pny154
|View full text |Cite
|
Sign up to set email alerts
|

Are Invasive Procedures Effective for Chronic Pain? A Systematic Review

Abstract: There is little evidence for the specific efficacy beyond sham for invasive procedures in chronic pain. A moderate amount of evidence does not support the use of invasive procedures as compared with sham procedures for patients with chronic back or knee pain. Given their high cost and safety concerns, more rigorous studies are required before invasive procedures are routinely used for patients with chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 56 publications
0
17
0
2
Order By: Relevance
“… 1 , 2 , 3 Effective, long‐term pharmacological, interventional, and surgical treatments remain elusive. 4 Spinal cord stimulation (SCS) is a well‐established treatment for chronic LBP and leg pain (LP). 5 , 6 Traditional SCS provides modest long‐term relief for patients with LBP.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 Effective, long‐term pharmacological, interventional, and surgical treatments remain elusive. 4 Spinal cord stimulation (SCS) is a well‐established treatment for chronic LBP and leg pain (LP). 5 , 6 Traditional SCS provides modest long‐term relief for patients with LBP.…”
Section: Introductionmentioning
confidence: 99%
“…24 A systematic review investigating the use of placebo compared with invasive procedures for chronic pain concluded a higher improvement for placebo over actual treatments. 25 The fact our results are statistically significant suggests our patients do see an improvement. However, to gauge the clinical impact of our results, we aim to add the following questionnaires: PROMIS-29, FSFI, and Absenteeism.…”
Section: Outcome Measurementsmentioning
confidence: 52%
“…Additionally, the reliability of the one‐dimensional VAS pain scale needs to be confirmed as there currently is not a universally agreed on minimum clinically important difference in chronic pain 24 . A systematic review investigating the use of placebo compared with invasive procedures for chronic pain concluded a higher improvement for placebo over actual treatments 25 . The fact our results are statistically significant suggests our patients do see an improvement.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, there is no evidence that use of opioids improves return to work or reduces the need for other treatments (21). In addition, a recent systematic review showed that real surgery is no better than sham surgery for CLBP (38). For these reasons, researchers and clinicians have during the last decade made an effort to change the paradigm of LBP, looking for possible causes and implementing new treatment approaches.…”
Section: A C C E P T E Dmentioning
confidence: 99%